Interactions of Concomitant Species of Nematodes and Fusarium oxysporum f. sp. vasinfectum on Cotton - Yang, Henry (Society of Nematologists, 1976)
Meloidogyne incognita, Hoplolaintus galeatus, and North Carolina and Georgia populations of Belonolaimus longicaudatus were introduced singly and in various combinations with Fusarium oxysporum f. sp. vasinfectum on wilt-susceptible 'Rowden' cotton. Of all the nematodes, the combination of the N. C. population of B. longicaudatus with Fusarium promoted greatest wilt development. H. galeatus had no effect on wilt. With Fusarium plus M. incognito or B. longicaudatus, high nematode levels promoted greater wilt than low levels. The combination of either population of B. longicaudatus with M. incognita and Fusarium induced greater wilt development than comparable inoculum densities of either nematode alone or where H. galeatus was substituted for either of these nematodes. Nematode reproduction was inversely related to wilt development. Without Fusarium, however, the high inoculum level resulted in greater reproduction of all nematode species on cotton. Combining M. incognita with B. longicaudatus or H. galeatus gave mutually depressive effects on final nematode populations. The interactions of H. gateatus with B. longicaudatus varied with two populations of the latter.